Enhancing Our Understanding of Ladybirds in Ireland – A Case Study of the Use of Citizen Science - Weyman, Gill; Butler, Fidelma; McKeown, Sean (Frontiers in Conservation Science, 2022)
Citizen science is increasingly recognised as a useful approach for gathering data, contributing to biodiversity awareness raising and creating meaningful engagement between citizens and professional scientists. In a number of countries, academic institutions have led the way in developing ladybird projects, incorporating citizen science, to increase distributional data on the species, as well as a greater understanding of ladybird ecology. The current research evaluates the role of citizen science campaigns in collecting biological distributional data in Ireland, using ladybirds as a case example, examining if citizen science records and the use of photographs can provide a valuable insight into our understanding of ladybird ecology. From April 2020 to June 2021, a citizen science programme engaged with the wider public, via social media networks to increase the number of ladybird records and assist in establishing national data baselines, since ladybird recording is a relatively new phenomenon in Ireland. This case study finds that citizen science projects using social media can increase the number of records of ladybirds and provide useful information on species distribution patterns. There were a disproportionate number of records from areas of high human population, resulting in a bias towards urban centres. Photographs submitted by members of the public provided a limited amount of information on food plants but indicated that ladybirds are valued as a species of interest to the public. These images can also help to increase records of the less common species, especially as members of the public may not be able to easily distinguish between different species of ladybirds.